Decomposition kinetics of alkali metal gallams in hydroxide aqueous solutions - Tikhomirov I. A. Ivan Arsentyevich; Lavrenyuk P. I.; Orlov A. A.; Vidyaev D. G. (2002, 2002)
The decomposition kinetics of alkali metal gallams in LiGa-LiOH, NaGa-NaOH, KGa-KOH, LiGa-NaOH, LiGa-KOH, and KGa-NaOH systems in the 40-80°C range was studied. The rate constant and current density of decomposition were determined. The rate equation of gallam decomposition under the given experimental conditions was obtained.